Effect of an In-Home Palivizumab Administration Program for Children with Medical Complexity - Hina Emanuel; Aravind Yadav; Julie C. Eapan; Maria Caldas-Vasquez; Tomika S. Harris; Katrina McBeth; Fatima Boricha; Janice John; Ivan G. Magana Ceballos.; Giuseppe N. Colasurdo; Maria E. Tellez; Tina Reddy; et al. (Children)
Background: In-home palivizumab administration programs (PH) have shown promise in reducing RSV-associated infections. These programs may be particularly beneficial for children with medical complexity (CMC) by limiting their exposure to healthcare-associated infections (HAIs) from non-RSV-related pathogens during transportation and visits to medical facilities. Methods: In this prospective study, 41 children with CMC less than 2 years of age were randomized by their health insurance to receive PH or in the clinic (PC) during the RSV season (October 2018–April 2019). Patients were stratified by home ventilation. The primary outcome was the total number of face-to-face encounters. Secondary outcomes were unscheduled clinic visits and hospitalizations secondary to the non-RSV LRTIs. Standard frequentist and Bayesian analyses were performed. Results: All demographic factors and strata were matched between PH (“n” = 13, mean age 22 mo. SD ± 1), and PC (“n” = 28, mean age: 18 mo. SD ± 1). There was a decrease in the number of total face-to-face encounters (adjusted for mechanical ventilation and baseline diagnosis) [(4.5 vs. 8.8), (RR: 1.8, 95% CI: 1.3–2.5, p = 0.001)], and hospitalizations [(0.3 vs. 1.25), (RR: 3.8, 95% CI: 1.3–11.3, p = 0.016)], in the PH vs PC groups. Bayesian analysis showed a 93% probability of benefit in favor of fewer face-to-face encounters in the PH group. Conclusions: This study suggests that PH administration may reduce healthcare utilization in CMC. Minimizing exposure to healthcare facilities and supporting home-based interventions are promising strategies for this population.